Controladoria e Modelo de Gestão Aplicados às Instituições de Ensino Superior - Ferreira, Leonardo Nunes (2001)
The establishment of the Nova Lei de Diretrizes e Bases da Educação Nacional (New Law of Policies and Basis of the National Education) was a mark for the Brazilian educational sector. The institutions of advanced education began to seek two major objectives: the continuous improvement of your academic, pedagogic and administrative practice and the elimination of resources waste. Beyond the implementation of the New Law of Policies and Basis of the National Education, many were the factors that contributed for the change of the paradigms of management of the Institutions of Advanced Education in Brazil. Some of these factors are the following: a) Increasing competition. The competition, each time more present in the day-to- day of the Institutions of Advanced Education, that was regional and closed by, it¿s now professional and global.b) Implantation of the mechanism of quality control, for example the Provão (Exam), by the Ministry of Education.c) Increasing demand for the advanced courses, since the number of students concluding the Middle level courses has being increasing gradually in the last years. d) Education has become a critical factor in the competition between nations, regions and companies.In the present moment, marked by intense competition, complex academic and administrative processes, technologic information as a condition ¿ sine qua non¿ for the decisive process and the exigency for modern and cooperated management, demands big changes in the way the educational institutions manage their resources and evaluate the performance of their administrators.The study demonstrates the pressing necessity of implanting a Control Management that will assist the administration of the Institution of Advanced Education in a way that will optimize the economic results of the entity, as well as the creation and implementation of the mechanisms that will bring a better understanding of the environment in which the entity lives and operates.